Antecedents of Trust and Its Consequences on Continuous Usage Intention E-Money - Putu Gede Denny Herlambang; Nyoman Dwika Ayu Amrita; I Made Kartika; I Kadek Sara Mandiyasa (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
This research is motivated by the development of technology in the field of information and communication which has an impact on the emergence of new innovations in terms of electronic payments. Non-cash money or electronic money (e-money) is a payment instrument that fulfills the elements, namely issued on the basis of the value of money deposited in advance by the holder to the issuer, the value of money is stored electronically in a medium such as a server or chip, used as a means of payment to merchants who are not the issuer of the electronic money and the value of electronic money deposited by the holder and managed by the issuer is not a deposit as referred to in the laws governing banking.The benefits and convenience offered by electronic money can influence the increase in users. When a product has benefits and convenience when used in everyday life, it is likely that the product will be used by the wider community. This study aims to explain the factors that influence trust and its consequences on continuous usage intention of e-money in Denpasar City in terms of perceived benefits, perceived convenience and perceived risk. Trust here acts as a mediating variable. The research sample was 100 people in Denpasar city. The research method used is quantitative method with PLS-based structural equation model analysis or SEM. This research shows that perceived benefits and perceived ease of use influence respondents confidence in using e-money continuously, while perceived risk does not show any influence on respondents confidence in their intention to use e-money continuously. Furthermore perceived benefits and perceived ese of use hav positive effect on the intention to continue using e-money, while perceived risk has no effect on the intention to use e-money continuously.